The evaluating the effectiveness of advertising controversial products on consumer purchase decision - Mhete, Patience (Midlands State University, 2017)
The study aimed at evaluating the effectiveness of advertising controversial products on consumer purchasing decisions with special reference to Savanna Tobacco Company and it was carried out from July 2015 to November 2015.The main aim of the study was to measure advertising techniques suitable for communicating controversial products in terms of consumer attitudes, purchase intentions and demand patterns. The research results followed guidance of three main objectives that are: examining the influence of sponsorship on consumer attitudes, to find out if endorsement affects purchasing intentions and to determine influence of bandwagon on demand patterns.Advertising of controversial products was perceived by Fay (1995), Waller (1999), Pendergus (2001) as a negative concept due to the nature of product where products such as cigarettes are perceived to be controversial that offends when advertised because they are related to anti-social behavior. Data capturing was done using exploratory and descriptive research designs using judgmental sampling. A targeted population of 300 respondents including 5 managers, 45 employees and 250 customers was used and research instruments used to gather information were questionnaires and interviews. When the results were analyzed it showed that most of the respondents from the population chosen were satisfied with usage of sponsorship, endorsement and bandwagon appeals in influencing their purchase decisions. The research concluded that advertising techniques used by Savanna Tobacco Company increased demand, purchase intentions and resulted in consumers having positive attitudes towards the company and its products. The researcher indicated that the three techniques (sponsorship, endorsements and bandwagon) are effective with bandwagon being the most effective one. Recommendations are that Savanna Tobacco Company should continue using these techniques but should also work on the product quality. Point of Sale (POS) advertising and product placement are other techniques which Savanna Tobacco Company can use to improve reach of their products.